2015
DOI: 10.1590/s1984-82502015000200024
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin calcium loaded chitosan nanoparticles: in vitro evaluation and in vivo pharmacokinetic studies in rabbits

Abstract: In this study, we prepared atorvastatin calcium (AVST) loaded chitosan nanoparticles to improve the oral bioavailability of the drug. Nanoparticles were prepared by solvent evaporation technique and evaluated for its particle size, entrapment efficiency, zeta potential, in vitro release and surface morphology by scanning electron microscopy (SEM). In addition, the pharmacokinetics of AVST from the optimized formulation (FT5) was compared with marketed immediate release formulation (Atorva ® ) in rabbits. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…In contrast to our study which SLN was designed for dermal delivery, their SLN has been suitable for oral delivery. Most of the studies carried out on atorvastatin solid lipid nanoparticles have been for oral delivery ( 35 38 ) rather than dermal or transdermal delivery. Depending on the composition of SLN varying particle size, zeta potential, PDI, and EE% can be obtained ( 35 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to our study which SLN was designed for dermal delivery, their SLN has been suitable for oral delivery. Most of the studies carried out on atorvastatin solid lipid nanoparticles have been for oral delivery ( 35 38 ) rather than dermal or transdermal delivery. Depending on the composition of SLN varying particle size, zeta potential, PDI, and EE% can be obtained ( 35 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…From these results, we concluded that the release of AT from F1 follows a zeroorder, diffusion, and swelling mechanism. 38 More than one mechanism exerts a dominant effect on the release pattern of the drug from biodegradable polymeric systems; for example, diffusion-controlled release from the matrix of polymers is followed by readsorption, then the drug is desorbed from the surface of formed NPs, leading to degradation and dissolution/erosion of the polymeric network. 52 Nevertheless, drug release from the formed NPs is a combination of drug diffusion and surface erosion; CS forms a coat that acts as a physical barrier that swells or erodes, consequently restraining the release of drug from NPs.…”
Section: Discussionmentioning
confidence: 99%
“…All formulations followed non-Fickian anomalous diffusion-controlled mechanism since values of n≥0.5, indicating diffusion-controlled and swelling-controlled drug release. 15,16,38 The in vivo results may be due to the unparalleled properties of CS that formed the nanoparticles, 61 including bioadhesivity and penetration enhancement. CS carries a positive charge, so the bioadhesive property is due to its interaction with the negatively charged mucin on the eye surface.…”
Section: Discussionmentioning
confidence: 99%
“…The mass of released atorvastatin was quantified using a spectrometer (Epoch 2 Microplate Spectrophotometer, BioTek, VT, USA) by checking the absorbance at 264 nm against appropriate standards. [31] Murine Hindlimb Ischemia Model: Experiments were performed on male eight-week-old BALB/c nude mice (Biogenomics, Seoul, Korea) maintained under a 12 h light/dark cycle and in accordance with the regulations of the Pusan National University. All procedures were performed in accordance with the policies of the Institutional Animal Care and Use Committee of the Pusan National University of Korea (IACUC090017).…”
Section: Fabrication Of Bbvs With 3d Coaxial Printing Techniquementioning
confidence: 99%